Argentina: entre la hiperinflación y la trampa de la liquidez. - Rubini, Héctor (2003)
In last 90*s Argentine Government has put in force an irrevocable fixed exchange rate regime and market reforms that were not able to endure. These ones were left out in 2002, and Argentine was to show features of economic underdevelopment, distributive inequality and institutional instability. The main hypothesis of this paper is that both the abandonment of that regime and the worsening Uf the sucial - economic situation are due to domestic policy mistakes, rather than to “external shocks”. Once upon the Convertibility was abandoned, if the society has“learned” from experience, there would not be scope for highly discretionary policies, because both the Government and the markets shall be conscious of the peril< of falling in either high-hyper inflation, or depressive deflation, like the so-called “tiquidity traps”. Provided those risks, the recovery of trust of institutions emerges as a necessary condition to help Argentina to emerge from the present crisis.